IMPACTS ON THE DUNES SYSTEM: NATURAL DYNAMIC VERSUS ANTHROPOGENIC INTERFERENCE - LUANA PORTZ; JOÃO PEDRO DE MOURA JARDIM; ROGÉRIO PORTANTIOLO MANZOLLI; NELSON SAMBAQUI GRUBER (Ambiente & Sociedade, 2016)
Abstract The shoreline of Capão da Canoa, RS, alternates densely populated areas with non urban empty spaces that still have their natural features preserved. This paperwork aimed to evaluate the foredunes vulnerability, by field evaluation along the shoreline in wintertime and summertime, using a field checklist. After rating some parameters, a Vulnerability Index was established for each profile. The highest values matched the most densely populated areas in that municipality, due to the position of the urban area that often shortens the width of the foredune ridges. The superiority of the wintertime vulnerability index when compared to summertime, changes the consensus about the human interference as the main vector of vulnerability. The major factors contributing to foredune degradation were: beach condition during winter time and use pressure, during summertime, indicating the high vulnerability associated with some profiles along the shoreline.